Avaliação de diferentes materiais de cobertura para construção dotelhado de aviários móveis - Joao Batista Matos Junior (2012)
This research aimed to: 1) was to test different materials of cover the roof of aviaries furniture on thermal comfort indices for birds; and 2)was to evaluate the surface temperature and cloacal broiler chickens raised in aviaries furniture, with different covers for the roof. To test different roofing materials for the roof aviaries were built three mobile mobile aviaries, with 2.0 m of length x 1.0 m width x 1.2 m height. The treatments were: 1) cardboard covered with plastic double-sided (white and black), and the white face turned to the outside and black face toward the interior, 2) cardboard covered with long life package (Tetra Pak ®) with metal face outward to the exterior, and 3) cover the roof with a blade formed by long-life package (Tetra Pak ®), with metal face toward to the exterior. The treatments were arranged in a randomized block design with 15 replications generated in time; with the blocks consist of the sampling days. There were collected for 15 consecutive days in September of 2010 in every two hours, from 10 to 18 hours inside thepoultry houses at a height of 0.70 from the ground, the index of black globe temperature and humidity (BGT), the dry bulb temperature (DBT), the heat load radiation (CTR), relative humidity (RH), the external surface temperature of the roof (EST)), the internal surface temperature of the roof (IST)) and the difference between the EST and IST (DIF). The roof which provided thermal comfort indexes compatible with the raising birds was the treatment with cardboard covered with plastic showing better results for the BGT comparison with the cardboard roofs covered with Tetra Pak ® package and roof formed with blade package of Tetra Pak ®. It is concluded that the roof of cardboard covered with plastic was the one that provided the best thermal comfort for the birds. To evaluate the surface temperature and cloacal broilers reared in aviaries furniture, with different covers for the roof were built two aviaries furniture with the same dimensions as the experimental one and the same experimental treatments 1 and 2. In each aviary furniture were housed 20 broiler females chicks the commercial line Label Rouge, 42 days of age in adesign similar to experiment 1.There were collected for 15 consecutive days in the month of October in 2011, at 12 hours the surface temperature and cloacal birds, the index of black globe temperature and humidity (BGT), the dry bulb temperature (DBT), the radiation heat load (CTR), relative humidity (RH). To evaluate the surface temperature and cloacal, they were randomly selected five birds from each experimental unit and recorded the temperatures of the wing, the cinnamon, the head and back of the birds, with the aid of an infrared thermometer. To determine the cloacal temperature, a digital thermometer was inserted into the cloaca of the birds at a depth of approximately 5 cm from where the temperature was measured. Treatment with plastic plus cardboard produced a better BGT, however, other environmental variables and the surface and cloacal temperatures were not affected by experimental treatments. It is concluded that coverage of cardboard covered with plastic provides better thermal environment for the birds, however experimental treatments do not change thermal homeostasis of the birds.